A new species of the genus Anahita Karsch, 1879 (Araneae: Ctenidae) from Hainan Island, China - Zhang, Feng; Hu, Dong-Sheng; Han, Guang-Xin (Zootaxa, 2011)
The spider genus Anahita Karsch, 1879 includes 21 species (Platnick 2011). There has been no revision of the genus and a recent cladistic analysis of the family Ctenidae (Silva 2003) suggested that Anahita was not monophyletic. However, Silva (2003) transferred Anahita isaloensis Ono, 1993 to Vulsor Simon, 1888 and now all species in the genus can be recognised by the absence of the retrolateral tibial apophysis and the presence of a hyaline area in the female epigynum. Fourteen species of Anahita are distributed in Africa, two species are reported from America and five species are known from Asia; A. fauna Karsch, 1879, A. maolan Zhu, Chen & Song, 1999, A. punctata (Thorell, 1890), A. samplexa Yin, Tang & Gong, 2000 and A. syriaca (O. Pickard-Cambridge, 1872). Four of the five Asian species have been described or redescribed recently (Song et al. 1999; Zhu et al. 1999; Yin et al. 2000; Levy 2003) and A. punctata is known only from a juvenile specimen collected in Sumatra, Indonesia (Thorell 1890).